Faktor-Faktor Yang Mempengaruhi Produksi Usaha Ternak Ayam Petelur Di Kecamatan Way Kenanga Kabupaten Tulang Bawang Barat - Dwi Lestari; Emi Maimunah (Journal on Education, 2023)
This study aims to determine the factors that influence production in laying hens in Way Kenanga District, West Tulang Bawang Regency. In this study the data were analyzed using a quantitative descriptive method. Primary data obtained through interviews and questionnaires. The analysis in this study uses the Cobb-Douglass production function model which is then estimated using the Ordinary Least Square (OLS) method. The dependent variable is egg production and the independent variables are the number of chickens, feed, labor, and cage area. The results show both partially and simultaneously that the variables of the number of chickens, feed, labor, and size of the cage have a positive and significant effect on egg production in Way Kenanga District, West Tulang Bawang Regency.